2006
DOI: 10.1345/aph.1g488
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Heart Rate Effects Following a Single Dose of Bitter Orange

Abstract: SBP, DBP, and HR were higher for up to 5 hours after a single dose of bitter orange versus placebo in young, healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 13 publications
3
72
2
Order By: Relevance
“…32 A few studies have shown the lipolytic activity of another component of orange juice, synephrine, 33,34 an adrenergic compound that could have adverse health effects. 35,36 Nevertheless, no difference in the amount of synephrine was found between Moro and Naveline juices. We cannot exclude, however, that anthocyanins synergize with synephrine, thus amplifying their activities on fat tissue.…”
Section: Discussionmentioning
confidence: 88%
“…32 A few studies have shown the lipolytic activity of another component of orange juice, synephrine, 33,34 an adrenergic compound that could have adverse health effects. 35,36 Nevertheless, no difference in the amount of synephrine was found between Moro and Naveline juices. We cannot exclude, however, that anthocyanins synergize with synephrine, thus amplifying their activities on fat tissue.…”
Section: Discussionmentioning
confidence: 88%
“…For example, the peel of bitter orange can cure nasal congestion and dyspepsia, an indigestion problem [83]. The oil and flower of bitter orange can be used to treat duodenal ulcers and constipation.…”
Section: Therapeutic Benefits Of Bitter Orangementioning
confidence: 99%
“…At the time of data collection, at least 1 year after completion of all projects included in the analysis, manuscripts from 12 projects (5.3% of total; 50% of those projects for which a manuscript had been submitted) had been accepted, and either was published or in press (Table 2). [6][7][8][9][10][11][12][13][14][15][16][17] A student served as the lead author on 8 of the publications, [6][7][8][12][13][14][15][16] and no students were authors on 2 of the publications.…”
Section: Resultsmentioning
confidence: 99%